The Effectiveness of Polling Station Supervisor Recruitment Based on Digital Literacy Competence for the SIWASLIH Application in Batam City - Sahat F. Rivai Lumban Toruan; Ampuan Situmeang; Hari Sutra Disemadi (CV. Social Politic Genius (SIGn), 2026)
The implementation of Regional Election oversight through the SIWASLIH application in Batam City continues to face operational constraints, barriers to digital adaptation, and limited supporting facilities for Polling Station Supervisors. This empirical legal research aims to evaluate the effectiveness of Polling Station Supervisor recruitment, analyze the determinants of recruitment dysfunction, and formulate optimization strategies based on digital literacy competence. Using a socio-legal approach, data were collected through in-depth interviews with seven informants and analyzed through a synthesis of legal system theory and legal effectiveness theory. The findings show that the ineffective use of SIWASLIH is caused by the absence of technical recruitment norms that explicitly assess the digital literacy competence of Polling Station Supervisors. Article 27 of Law Number 8 of 2015 provides the normative basis for the duties, authorities, and reporting obligations of Polling Station Supervisors. However, the implementation of these obligations through SIWASLIH has not been supported by adequate digital selection instruments under Bawaslu Regulation Number 19 of 2017 or Decree of the Chairperson of Bawaslu Number 301/HK.01.01/K1/09/2024. The absence of these technical indicators causes recruitment to rely on administrative assessment and general interviews. This study recommends revising technical recruitment instruments, affirming digital literacy indicators in Bawaslu regulations, developing SIWASLIH with offline functionality, providing practice-based technical training, and establishing a task force for technological assistance.